Training and tool supply to enhance food safety behaviors among ready-to-eat chicken vendors in informal markets in Ouagadougou, Burkina Faso: a randomized-controlled trial - Madjdian, D.S.; Asseldonk, M. van; Ilboudo, Guy S.; Dione, Michel M.; Ouedraogo, A.-A.; Roesel, Kristina; Grace, Delia; Talsma, E.F.; Knight-Jones, Theodore J.D.; Vet, E. de (Elsevier, 2024)
In Burkina Faso, street food vendors are key in ensuring food safety in urban markets, particularly within the poultry value chain. The sale of high-risk ready-to-eat chicken by these vendors poses substantial health hazards, emphasizing the urgency for capacity-building to enhance food safety practices. This study evaluated the effect of a participatory interactive three-day training program coupled with tool supply, on self-reported and observed behavior, and knowledge, attitudes, and cognitions vendors of street ready-to-eat chicken in Ouagadougou’s informal markets. A two-armed RCT was conducted, including pre- and post-training vendor surveys, along with direct outlet observations. Total sample size comprised 162 vendors, with 72 in the treatment group and 90 in the control group. Self-reported behavior - measured on a 5-point scale - significantly improved in the treatment group including higher frequency of mask wearing (1.8±0.8 vs 2.5±1.2, p<0.001) and inspecting nail hygiene (4.3±0.8 vs. 4.7±0.6, p<0.001). Treatment outlets improved on securing adequate evisceration platforms (1.3±0.6 vs. 1.0±0.5, p=0.054) regular carcass water renewal (61.8% vs. 36.4%, p=0.038), and handwashing during carcass management (1.1±0.5 vs. 0.9±0.3, p=0.008). Better adherence to handwashing (1.1±0.4 vs. 0.9±0.3, p=0.051), fork use (58.9% vs. 41.8%, p=0.029), proper handwashing facilities (38.4% vs. 20.9%, p=0.014), and waste management (64.4% vs. 37.8%, p<0.001) were observed in treatment outlets. Trained vendors scored significantly higher than controls on knowledge (effect size 0.75, p<0.001). Vendors rated the perceived usefulness and perceived ease of use, trust in materials/tools, measured on a 5-point scale, as high and perceived mean increased daily profits (21242 FCFA) and number of customers (8.3) following training. In conclusion, training combined with a tool package proved effective in fostering significant food safety behavior changes, underscoring its substantial impact beyond just knowledge enhancement. For lasting behavior changes, ongoing training and support, an enabling environment, and strong incentives that prioritize vendor food safety behaviors informal markets are crucial.